2019
DOI: 10.4049/jimmunol.1800848
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus–Induced Imbalance of Inflammatory and Antiviral Signaling by Differential Phosphorylation of STAT1 in Human Monocytes

Abstract: It is not clear how hepatitis B virus (HBV) modulates host immunity during chronic infection. In addition to the key mediators of inflammatory response in viral infection, monocytes also express a high-level IFN-stimulated gene, CH25H, upon response to IFN-α exerting an antiviral effect. In this study, the mechanism by which HBV manipulates IFN signaling in human monocytes was investigated. We observed that monocytes from chronic hepatitis B patients express lower levels of IFN signaling/stimulated genes and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 56 publications
(57 reference statements)
1
34
0
Order By: Relevance
“…Accordingly, HBV-induced production of inflammatory cytokines in monocytes depends on TLR2/MyD88/NFκB signaling. (25) Although the initial immune responses were transient in vitro, it is likely that this innate signaling in vivo is one of the first steps in a line of defense mechanisms leading to HBV clearance. Pathogen recognition receptors play a central role in innate immunity and have been recognized to affect chronic viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, HBV-induced production of inflammatory cytokines in monocytes depends on TLR2/MyD88/NFκB signaling. (25) Although the initial immune responses were transient in vitro, it is likely that this innate signaling in vivo is one of the first steps in a line of defense mechanisms leading to HBV clearance. Pathogen recognition receptors play a central role in innate immunity and have been recognized to affect chronic viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…(37) Interestingly, Song et al showed that whole HBV particles as well as HBsAg, purified from human plasma, activate TLR2 signaling in monocytes. (25) This leads to suggest that naturally occurring HBsAg, but not a recombinant one, harbors TLR2-activating potential. Here, HBV particles on the whole efficiently triggered TLR2mediated inflammatory responses in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further experiments in vitro showed that HBsAg or HBV directly induced the expression of PD-L1 and HLA-E and the secretion of anti-inflammatory cytokines of monocytes from healthy adults[11]. Our group recently reported that HBV induces monocyte production of inflammatory cytokines via TLR2/MyD88/NF-κB signaling and STAT1-Ser727 phosphorylation and inhibits interferon (IFN)-α-induced stat1, stat2, and ch25h expression through the inhibition of STAT1-Tyr701 phosphorylation and in an IL-10-dependent, partially autocrine manner[12]. Therefore, HBV-induced suppressive monocytes/macrophages play a key role in the immune pathogenesis of chronic persistent infection.…”
Section: Hbv-induced Immune Suppression Contributes To Persistent Infmentioning
confidence: 99%